2018
DOI: 10.1111/cei.13219
|View full text |Cite
|
Sign up to set email alerts
|

Blood immune cell biomarkers in lung cancer

Abstract: Summary Characterization of host immune cell parameters prior to treatment is expected to identify biomarkers predictive of clinical outcome as well as to elucidate why some patients fail to respond to immunotherapy. We monitored blood immune cells from 58 patients with non‐small‐ cell lung cancer (NSCLC) undergoing surgery of the primary tumor and from 50 age‐matched healthy volunteers. Complete leukocyte blood count, the number of circulating dendritic cells (DC), HLA‐DRlow monocytes and several lymphocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 50 publications
(56 reference statements)
4
43
0
Order By: Relevance
“…More recent studies have shown that an early decrease in NLR during treatment with PD‐1 inhibitors predicts its efficacy . NLR and ANC have been reported to correlate with the number of circulating MDSCs and tumor‐associated neutrophils, which suppress the function of antitumor T cells . Circulating MDSC levels were inversely associated with response rate and survival after treatment with nivolumab in cancer patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have shown that an early decrease in NLR during treatment with PD‐1 inhibitors predicts its efficacy . NLR and ANC have been reported to correlate with the number of circulating MDSCs and tumor‐associated neutrophils, which suppress the function of antitumor T cells . Circulating MDSC levels were inversely associated with response rate and survival after treatment with nivolumab in cancer patients .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the neutrophil‐to‐lymphocyte ratio (NLR) and the absolute neutrophil count (ANC) in the blood can predict the efficacy of PD‐1 inhibitors in patients with NSCLC . NLR and ANC have also been reported to reflect the number of circulating myeloid‐derived suppressor cells (MDSCs) and tumor‐associated neutrophils, which inhibit the function of antitumor T cells . The immunosuppressive status in the tumor microenvironment could be monitored using the dynamics of NLR and ANC.…”
Section: Introductionmentioning
confidence: 99%
“…In general, although with some level of heterogeneity, circulating pDCs are decreased in human cancer patients compared to healthy donors, particularly in advanced stage diseases, with a single relevant exception in a study of non-small-cell lung cancer (NSCLC) [144]. Specifically, the peripheral blood pDCs resulted decreased in cohort studies from ovarian cancer [137], NSCLC [145], bladder cancer [146], CRC [147] and advanced breast cancer patients [148]. Notably, in ovarian cancer, circulating pDCs are partially restored after complete remission by chemotherapy [137].…”
Section: Clinical Significance Of the Pdcs Compartment In Human Cancementioning
confidence: 99%
“…CD3+CD4+ absolute number also affects the treatment effect and prognosis of disease. Predicting long-term DFS of cancer patients immediately after surgical resection of clinically localized and advanced disease is of great value for patient counseling, identifying poor risk-group who might bene t from enrollment in adjuvant therapy protocols [33]. Prognosis of cancer patients is based not only on tumor-related factors, but also on host-related factors, including systemic immune cell activation [34].…”
Section: Al Affecting Disease-free Survivalmentioning
confidence: 99%